L’essor et le déclin de la stratégie économique keynésienne – structuraliste au Mexique - Julio López G. (Revue de la Régulation, 2012)
The aim of this paper is to study the proximate causes as well as the historical origins of the downfall of the Mexican “economic miracle”, which took place approximately between 1950 and the mid-1970s. The author shares a view that holds that in the mid-1970s, Mexico’s previous growth strategy faded, and that sees the economic troubles as an expression of the exhaustion of that strategy. He shows how this economic exhaustion came about by considering the supply and demands limits to fast growth in an international context that deteriorated, especially when the import substitution strategy reached a relatively advanced stage. He then considers the relationship between economics and politics during the “miracle” period as much as in the following years, arguing that fast and stable growth also served as material support for an alliance between the upper classes and the political bureaucracy. Thus, the demise of the previous economic model also eroded the material and ideological framework that made possible or eased the class alliance built during the “miracle” years.